2010
DOI: 10.2215/cjn.02570310
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Health Utility among 60-Day Survivors of Acute Kidney Injury in the Veterans Affairs/National Institutes of Health Acute Renal Failure Trial Network Study

Abstract: Background and objectives: Health-related quality of life (HRQOL) after acute kidney injury (AKI) is an area of great importance to patients. It was hypothesized that HRQOL after AKI would relate to intensity of dialysis during AKI and dialysis dependence at follow-up.Design, setting, participants, & measurements: The Veterans Affairs/National Institutes of Health Acute Renal Failure Trial Network Study was a multicenter, prospective, randomized trial of intensive versus less intensive renal replacement therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 36 publications
5
49
2
2
Order By: Relevance
“…Survivors of AKI were found to have a utility of 0.40 with a standard deviation of 0.37 at 60 days. We did not find evidence of improved health utilities over the 5 year period 11 . The health utility of death was valued at 0 9 .…”
Section: Methodscontrasting
confidence: 78%
“…Survivors of AKI were found to have a utility of 0.40 with a standard deviation of 0.37 at 60 days. We did not find evidence of improved health utilities over the 5 year period 11 . The health utility of death was valued at 0 9 .…”
Section: Methodscontrasting
confidence: 78%
“…Cr and BUN were the classical standards to evaluate renal damage (34). Accordingly, Hsu et al demonstrated the observation of elevated Cr in an atypical antipsychotic drug administration (35).…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) requiring dialysis occurs in 1% to 4% of hospitalized patients and, in the setting of multisystem organ failure, is associated with exceptionally high morbidity and mortality (1)(2)(3). To date, there is no specific treatment for AKI.…”
Section: Introductionmentioning
confidence: 99%